Prospective investigation of carbapenem-resistant Klebsiella pneumonia transmission among the staff, environment and patients in five major intensive care units, Beijing. Issue 2 (February 2019) - Yan, Zhongqiang; Zhou, Yu; Du, Mingmei; Bai, Yanling; Liu, Bowei; Gong, Meiliang; Song, Hongbin; Tong, Yigang; Liu, Yunxi
Summary: Background: Following the alarming outbreak of carbapenem-resistant Klebsiella pneumonia (CRKP) in five intensive care units (ICUs) of a tertiary care hospital in China, a prospective investigation of CRKP colonized/infected patients was conducted. Aim: To describe the diffusion and transmission of CRKP among epidemiologically linked ICU patients, staff and environment. Methods: Enhanced CRKP infected/colonized case monitoring was performed by the real-time nosocomial infection surveillance system (RT-NISS). The immediate surroundings of each CRKP patient bed unit and the staff hands/gloves/gowns were sampled and then evaluated for the presence of CRKP. Antimicrobial susceptibility tests, pulsed-field gel electrophoresis (PFGE) and whole-genome sequencing (WGS) were used to identify and to characterize these isolates. Findings: Among 2750 patients monitored, 67 CRKP patients were newly labeled and 11 patients' CRKP isolates were available. A total of 31.34% (21/67) bed units were positive at one or more surrounding surfaces, 7.99% (49/613) environmental samples and 3.57% (4/112) ICU staff samples were CRKP positive. The selected CRKP isolates ( N  = 64) exhibited intermediate to high resistance levels to the antibiotics tested apart from colistin and tigecycline. RT-NISS data combined with MLST and PFGE revealed nine likely transmission clusters. WGS analysis of these CRKP isolates revealed extensive sharing of multiple antimicrobial resistance genes and plasmid replicons among these isolates. Two carbapenemase genes bla KPC-2 (62/64) and bla OXA-48 (2/64) were identified. These CRKP isolates carried one or more plasmid replicons. Conclusions: The contamination of ICU environment and staff's hands, gloves or gowns is frequent with CRKP patients. Our study also supports the hypothesis that an association between environmental contamination and transmission of CRKP bacteria in ICUs.